Additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks

By using raw materials such as waste concrete, oil-based ash slag and phosphogypsum, combined with microwave treatment, electrostatic mixing, laser additive manufacturing and tomographic laser scanning technology, the problems of poor performance of hollow bricks and industrial solid waste pollution are solved, and high-strength and multifunctional hollow brick preparation is achieved.

CN118682878BActive Publication Date: 2025-03-18CHONGQING JIAOTONG UNIV +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411169668.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-24
Publication Date
2025-03-18
Estimated Expiration
2044-08-24

AI Technical Summary

Technical Problem

The existing hollow brick preparation process has problems such as poor product performance and inability to customize the internal complex structure and precise control. At the same time, industrial solid waste such as oil-based ash slag and phosphogypsum have serious environmental pollution and resource waste.

Method used

Use waste concrete, oil-based ash slag and phosphogypsum as raw materials, and improve material uniformity through microwave treatment and electrostatic mixing technology, combine laser-assisted additive manufacturing and tomographic laser scanning technology to achieve high-precision molding of complex structures, and reduce thermal shock through phased sintering process to ensure product structural integrity.

Benefits of technology

It has achieved high strength, high density, low water absorption of hollow bricks, and can meet quality standards. It can also manufacture complex structures and multifunctional hollow bricks according to needs, solving the problems of environmental pollution and resource waste in industrial solid waste.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses an additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, which adopts laser-assisted additive manufacturing and tomographic laser scanning to connect brick body molding, realizes high-precision and high-efficiency molding, has high strength and controllable structure, and significantly improves the performance and manufacturing flexibility of the product. The compressive strength of the hollow bricks prepared by the present invention can reach 14.6MPa, has high density and low water absorption, and meets the quality standards of hollow bricks. And the present invention can manufacture hollow bricks with complex structures according to actual needs, so that it has multifunctionality, which is suitable for the development of complex structures and multifunctional products. The present invention uses solid waste as raw materials, has low cost, is environmentally friendly and energy-saving, has simple process, and is easy to promote and use. The present invention brings outstanding benefits to society and the environment, and at the same time realizes the efficient resource utilization of wastes such as oil-based drill cuttings ash, turning waste into treasure, and has broad market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks. Background Art

[0002] Hollow bricks are made of clay, shale and other raw materials, and are processed, formed and sintered. Compared with solid bricks, hollow bricks can save a lot of land and fuel for burning bricks, reduce transportation weight; reduce the labor intensity during brick making and masonry, speed up construction progress; reduce the weight of buildings, increase the number of floors and reduce construction costs. In recent years, hollow bricks have become the first product recommended by the national construction department due to their advantages such as light weight and low consumption of raw materials, and have become the main wall material commonly used in the construction industry.

[0003] At present, the use of industrial waste, waste residue, etc. to produce hollow bricks has become the main research direction, because the use of industrial solid waste as raw materials to produce hollow bricks not only helps to realize the comprehensive utilization of industrial waste, promote energy conservation and emission reduction, but also reduces enterprise costs. For example, the invention patent CN105948698A discloses a sintered clay hollow brick for use in severe cold areas and its preparation method, which is a clay sintered hollow brick made of raw materials such as salt gypsum, coal mud, solid waste phosphating slag, waste cotton pulp, and ash calcium powder. The invention patent CN111848077A relates to a solid waste-based non-fired environmentally friendly hollow brick and its preparation method, which uses red mud, mineral powder, industrial by-product gypsum, fly ash, silica ash, aluminum ash, carbide slag and wastewater as the main raw materials. However, hollow bricks prepared using solid waste generally have the disadvantage of low mechanical strength. The conventional production lines of hollow bricks are all molded, with a simple structure and a single function, which cannot meet the needs of the market. In addition, the complex internal structure of hollow bricks cannot be quickly customized and the brick structure cannot be accurately controlled, which limits the development of complex and multifunctional products.

[0004] Laser-assisted additive manufacturing (LAAM) technology builds three-dimensional entities by adding materials layer by layer, allowing complex shapes and fine structures of alloys to be manufactured efficiently and accurately. In the LAAM process, the laser beam acts as a heat source to melt powder or wire and deposit it layer by layer to form the required alloy parts. It is mostly used in metal manufacturing, but it is rarely reported in the field of construction. The current LAAM method cannot monitor the additive manufacturing process, especially when the component structure is complex, and subtle differences in the environment and equipment will lead to a low component yield.

[0005] Phosphogypsum is a solid waste produced in phosphorus chemical production, and its main component is CaSO 4 ·2H 2O, my country's phosphorus chemical industry discharges about 50 million tons of phosphogypsum each year, accounting for more than 70% of industrial by-product gypsum, and it is growing at a rate of 15% per year. At present, the cumulative stockpile of phosphogypsum in the country exceeds 1.2 billion tons. Although it has been treated by many parties, most of it is still directly discarded and piled up, which not only occupies a large amount of land, but also causes environmental pollution. It has become a global problem that troubles the healthy development of the phosphating industry. For a long time, phosphate fertilizer companies have mainly adopted the stockpile method for treatment, and the comprehensive utilization rate is only about 10%. Oil-based drill cuttings are an oil-containing solid pollutant composed of petroleum, water and rock cuttings produced during shale gas drilling. Due to its large changes in properties and complex composition, it is more harmful to the environment and is therefore included in the list of hazardous wastes. Usually, the ash obtained after heating and degreasing the oil-based drill cuttings is discarded or used as a low-end inorganic filler. If it cannot be properly disposed of, it will still cause great pollution and difficulties, and it is a serious waste of resources. However, there are few reports on the resource utilization of oil-based ash. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is: how to provide an additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks to solve the problems that the existing preparation process generally has poor product performance, the inability to customize settings and precise control for hollow bricks with complex internal structures, and the serious environmental pollution and resource waste caused by industrial solid wastes such as oil-based ash and phosphogypsum.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solution: an additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, comprising the following steps:

[0008] S1: waste concrete recycled powder, phosphogypsum, oil-based ash and functional additives are mixed, and then mixed evenly by electrostatic field to obtain a mixture; the moisture content of the phosphogypsum is reduced to 2-5% after microwave treatment, and the particles of the oil-based ash are below 0.3 mm; the functional additive refers to an additive with a specific function of lifting hollow bricks.

[0009] S2: Use computer software to perform three-dimensional modeling of the actual structure of the target hollow brick to generate a processing program, then perform preset path planning and input it into the control system, then place the mixture obtained in step S1 in the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path to obtain a molded brick blank; specifically, lay the mixture on the laser-assisted additive manufacturing table through the feeding system to form a first layer of raw material layer, and use a laser to emit a high-energy laser beam, and use a scanning galvanometer to scan the raw material layer according to the preset path. The energy of the laser beam causes the raw material to melt rapidly and combine into a solid. After the first layer is formed, the feeding system lays another layer of the mixture, and repeats the above laser scanning process, stacking layer by layer according to the preset structure until the entire brick blank is formed.

[0010] S3: The brick blank formed in step S2 is subjected to infrared drying to make it dry evenly, and then the dried brick blank is sent to a sintering furnace for sintering. The sintering furnace is also connected to a tomographic laser scanning module, which can detect the internal structure of the hollow brick and feed back the structural information to the control system of the laser-assisted additive manufacturing, so as to adjust the relevant parameters in the next hollow brick forming process to achieve the target structure. After the sintering reaction is completed, the hollow brick can be obtained after the specimen cools down by itself. Among them, the moisture content of the brick blank is monitored in real time during infrared drying to ensure uniform drying and avoid cracking and deformation.

[0011] Preferably, the mixture comprises the following components in parts by weight: 35-50 parts of phosphogypsum, 30-45 parts of waste concrete, 10-20 parts of oil-based ash and 5-10 parts of functional additives.

[0012] Preferably, the functional additive includes one or more of silicon dioxide, bauxite or zirconium oxide. Adding silicon dioxide can improve the strength and wear resistance of hollow bricks; bauxite can improve the thermal insulation performance of hollow bricks.

[0013] Preferably, during the microwave treatment, the microwave frequency is 2400-2500 MHz, and the treatment time is 5-10 min.

[0014] Preferably, the electrostatic field action time is 10 to 20 minutes.

[0015] Preferably, the drying temperature during infrared drying is 60-80° C., and the drying time is 1-2 hours.

[0016] Preferably, the sintering process is heated in stages, which can effectively reduce the thermal shock encountered by the material during the sintering process and reduce the thermal stress caused by the rapid temperature change, which helps to avoid cracks and deformation and ensure the structural integrity of the final product. The initial low temperature stage (first reaching the temperature of 100-120°C within 20-30 minutes) is used to remove moisture and volatiles in the material to prevent cracks caused by too fast evaporation of water. The mid-term temperature rise stage (reaching the temperature of 300-310°C within 2.5-3 hours) is used to further drive out the remaining volatiles and enhance the adhesion of the material. The high temperature stage (reaching the temperature of 800-900°C within 5-6 hours) realizes the preliminary sintering of the particles and improves the microstructure of the material. The heat preservation stage (reaching the temperature of 950-1000°C within 1.5-2 hours and keeping warm for 20-30 minutes) can promote the uniform growth of the grains of the material and improve the mechanical properties and durability of the material. Specifically, during the high-temperature sintering process, the calcium-based components in the waste concrete react with the silicon and aluminum components in the oil-based ash to form silicate and aluminate phases with high strength and good stability. In addition, the calcium sulfate in the phosphogypsum decomposes at high temperatures to release SO 3 , which can form new mineral phases with other oxides, such as calcium sulfoaluminate, which have higher strength and stability.

[0017] Preferably, the relevant parameters in step S3 include laser power, scanning speed, powder feeding rate, layer thickness or powder spreading speed.

[0018] Another object of the present invention is to provide a hollow brick prepared by the above method.

[0019] Another object of the present invention is to provide application of the hollow bricks in the construction of frame structure buildings.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention uses waste concrete, oil-based ash and phosphogypsum as raw materials to prepare hollow bricks. The uniformity of the materials is enhanced by microwave treatment and electrostatic mixing technology, so that the mixture has good dispersibility and consistency. The interaction between the mixtures after high-temperature sintering effectively improves the strength of the hollow brick products. Laser-assisted additive manufacturing realizes high-precision molding of complex structures. At the same time, the staged sintering process effectively reduces thermal shock, reduces the risk of cracks, and improves the structural integrity and durability of the brick body. The efficient infrared drying process ensures the uniform drying of the brick body, further improving production stability and product quality. The compressive strength of the hollow bricks prepared by the present invention can reach 14.6MPa, with high density and low water absorption, which meets the quality standards of hollow bricks. In addition, the present invention can manufacture hollow bricks with complex structures according to actual needs, making them multifunctional, such as structures with specific holes and channels inside, to improve the thermal insulation performance of bricks, and is suitable for the development of complex structures and multifunctional products.

[0022] 2. The preparation process of the present invention uses laser-assisted additive manufacturing and tomographic laser scanning to connect brick body forming. On the one hand, it can realize the customization of hollow brick structure and use the set program to control the preparation of hollow bricks with different complex structures; on the other hand, it can realize the monitoring of the additive manufacturing process and conduct feedback processing, so as to carry out targeted regulation of the processing process to optimize the entire processing process in real time, so that the production process can have a self-repairing function, thereby adjusting the structure of the hollow brick and improving the final yield of the component. Therefore, the present invention realizes high-precision and high-efficiency forming, which significantly improves the performance and manufacturing flexibility of the product.

[0023] 3. The hollow bricks prepared by the present invention are mainly made of recycled concrete micropowder, phosphogypsum and oil-based ash slag, etc., with a large amount of admixture, which effectively solves the problem of solid waste discharge and disposal, reduces the land for solid waste stacking, saves the cost of solid waste treatment, creates considerable economic benefits for enterprises, brings outstanding benefits to society and the environment, and realizes large-scale and efficient resource utilization of waste such as oil-based ash slag, turning waste into treasure, and has broad market prospects. The product of the present invention has high strength performance, low cost, environmental protection and energy saving, simple process, and is easy to promote and use. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In the following examples, if no specific conditions are specified, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. The raw materials, equipment or instruments used, if the manufacturer is not specified, are all conventional products that can be obtained commercially.

[0025] Example 1: An additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, using the following steps:

[0026] S1: Place the phosphogypsum in a microwave treatment device with a microwave frequency of 2450 MHz and a treatment time of 7 minutes to reduce its moisture content to 3%. Use a jet milling device to crush the oil-based ash to less than 0.15 mm.

[0027] S2: Weigh 45 parts of phosphogypsum, 35 parts of waste concrete, 15 parts of oil-based ash and 7 parts of functional additives according to their weight, then place all the raw materials in an electrostatic mixing device, mix them for 15 minutes under the action of an electrostatic field to ensure that the components are evenly distributed, and obtain a mixture.

[0028] S3: Use computer software to perform three-dimensional modeling of the actual internal structure of the target hollow brick to generate a processing program, then perform preset path planning and input into the control system, then place the mixture obtained in step S2 in the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path, and lay the mixture on the laser-assisted additive manufacturing table through the feeding system to form the first layer of raw materials, use the laser to emit a high-energy laser beam, and scan the raw material layer according to the preset path through the scanning galvanometer. The energy of the laser beam causes the raw materials to melt rapidly and combine into a solid; after the first layer is formed, the feeding system lays another layer of mixture, and repeats the above laser scanning process. Stack layer by layer according to the preset structure until the entire brick is formed.

[0029] S4: Place the formed bricks in an infrared drying device, control the drying temperature at 70°C, and dry for 1.5 hours. Monitor the moisture content of the bricks in real time to ensure uniform drying and avoid cracking and deformation.

[0030] S5: The dried bricks are sent to the sintering furnace, and the temperature is first raised to 110°C for 30 minutes, then to 300°C for 3 hours, and then to 800°C within the next 6 hours. After 2 hours, the temperature reaches 1000°C, and the heating is stopped after keeping warm for 30 minutes. The sintering process is monitored by tomography to understand the internal structure of the sintered bricks, and the structural information is fed back to the laser-assisted additive manufacturing station, so as to adjust the forming process of the hollow bricks to achieve the target structure. After the reaction is completed, the specimen is cooled by itself to obtain the sintered hollow bricks.

[0031] Example 2: An additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, using the following steps:

[0032] S1: Place the phosphogypsum in a microwave treatment device with a microwave frequency of 2450 MHz and a treatment time of 7 minutes to reduce its moisture content to 3%. Use a jet milling device to crush the oil-based ash to less than 0.15 mm.

[0033] S2: Weigh 50 parts of phosphogypsum, 35 parts of waste concrete, 15 parts of oil-based ash and 7 parts of functional additives according to their weight, then place all the raw materials in an electrostatic mixing device, mix them for 15 minutes under the action of an electrostatic field to ensure that the components are evenly distributed, and obtain a mixture.

[0034] S3: Use computer software to perform three-dimensional modeling of the actual internal structure of the target hollow brick to generate a processing program, then perform preset path planning and input into the control system, then place the mixture obtained in step S2 in the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path, lay the mixture on the laser-assisted additive manufacturing table to form the first layer of raw material, use the laser to emit a high-energy laser beam, and scan the raw material layer according to the preset path through the scanning galvanometer. The energy of the laser beam causes the raw material to melt rapidly and combine into a solid; after the first layer is formed, the feeding system lays another layer of mixture, and repeats the above laser scanning process. Stack layer by layer according to the preset structure until the entire brick is formed.

[0035] S4: Place the formed bricks in an infrared drying device, control the drying temperature at 70°C, and dry for 1.5 hours. Monitor the moisture content of the bricks in real time to ensure uniform drying and avoid cracking and deformation.

[0036] S5: The dried bricks are sent to the sintering furnace, and the temperature reaches 110°C in 30 minutes, then 300°C in 3 hours, and then 800°C in the next 6 hours. After 2 hours, the temperature reaches 1000°C, and the heating is stopped after 30 minutes of insulation. The sintering process is monitored by tomography to understand the internal structure of the sintered bricks, and the structural information is fed back to the laser-assisted additive manufacturing station, so as to adjust the forming process of the hollow bricks to achieve the target structure. After the reaction is completed, the sintered hollow bricks can be obtained after the specimen cools down by itself.

[0037] Example 3: An additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, using the following steps:

[0038] S1: Place the phosphogypsum in a microwave treatment device with a microwave frequency of 2450 MHz and a treatment time of 7 minutes to reduce its moisture content to 3%. Use a jet milling device to crush the oil-based ash to less than 0.15 mm.

[0039] S2: Weigh 45 parts of phosphogypsum, 45 parts of waste concrete, 15 parts of oil-based ash and 7 parts of functional additives according to their weight, then place all the raw materials in an electrostatic mixing device, mix them for 15 minutes under the action of an electrostatic field to ensure that the components are evenly distributed, and obtain a mixture.

[0040] S3: Use computer software to perform three-dimensional modeling of the actual internal structure of the target hollow brick to generate a processing program, then perform preset path planning and input into the control system, then place the mixture obtained in step S2 in the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path, lay the mixture on the laser-assisted additive manufacturing table to form the first layer of raw material, use the laser to emit a high-energy laser beam, and scan the raw material layer according to the preset path through the scanning galvanometer. The energy of the laser beam causes the raw material to melt rapidly and combine into a solid; after the first layer is formed, the feeding system lays another layer of mixture, and repeats the above laser scanning process. Stack layer by layer according to the preset structure until the entire brick is formed.

[0041] S4: Place the formed bricks in an infrared drying device, control the drying temperature at 70°C, and dry for 1.5 hours. Monitor the moisture content of the bricks in real time to ensure uniform drying and avoid cracking and deformation.

[0042] S5: The dried bricks are sent to the sintering furnace, and the temperature reaches 110°C in 30 minutes, then 300°C in 3 hours, and then 800°C in the next 6 hours. Then, after the temperature reaches 1000°C after 2 hours, the heating is stopped after keeping warm for 30 minutes. The sintering process is monitored by tomography to understand the internal structure of the sintered bricks, and the structural information is fed back to the laser-assisted additive manufacturing station, so as to adjust the forming process of the hollow bricks to achieve the target structure. After the reaction is completed, the sintered hollow bricks can be obtained after the specimen cools down by itself.

[0043] Example 4: An additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, using the following steps:

[0044] S1: Place the phosphogypsum in a microwave treatment device with a microwave frequency of 2450 MHz and a treatment time of 7 minutes to reduce its moisture content to 3%. Use a jet milling device to crush the oil-based ash to less than 0.15 mm.

[0045] S2: Weigh 45 parts of phosphogypsum, 35 parts of waste concrete, 15 parts of oil-based ash and 7 parts of functional additives according to their weight, then place all the raw materials in an electrostatic mixing device, mix them for 15 minutes under the action of an electrostatic field to ensure that the components are evenly distributed, and obtain a mixture.

[0046] S3: Use computer software to perform three-dimensional modeling of the actual internal structure of the target hollow brick to generate a processing program, then perform preset path planning and input into the control system, then place the mixture obtained in step S2 in the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path, lay the mixture on the laser-assisted additive manufacturing table to form the first layer of raw material, use the laser to emit a high-energy laser beam, and scan the raw material layer according to the preset path through the scanning galvanometer. The energy of the laser beam causes the raw material to melt rapidly and combine into a solid; after the first layer is formed, the feeding system lays another layer of mixture, and repeats the above laser scanning process. Stack layer by layer according to the preset structure until the entire brick is formed.

[0047] S4: Place the formed bricks in an infrared drying device, control the drying temperature at 80°C, and dry for 1.5 hours. Monitor the moisture content of the bricks in real time to ensure uniform drying and avoid cracking and deformation.

[0048] S5: The dried bricks are sent to the sintering furnace, and the temperature reaches 110°C in 30 minutes, then 300°C in 3 hours, and 800°C in the next 6 hours. After 2 hours, the temperature reaches 1000°C, and the heating is stopped after 30 minutes of insulation. The sintering process is monitored by tomography to understand the internal structure of the sintered bricks, and the structural information is fed back to the laser-assisted additive manufacturing station, so as to adjust the forming process of the hollow bricks to achieve the target structure. After the reaction is completed, the sintered hollow bricks can be obtained after the specimen cools down by itself.

[0049] Example 5: An additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, using the following steps:

[0050] S1: Place the phosphogypsum in a microwave treatment device with a microwave frequency of 2450 MHz and a treatment time of 7 minutes to reduce its moisture content to 3%. Use a jet milling device to crush the oil-based ash to less than 0.15 mm.

[0051] S2: Weigh 45 parts of phosphogypsum, 35 parts of waste concrete, 15 parts of oil-based ash and 7 parts of functional additives according to their weight, then place all the raw materials in an electrostatic mixing device, mix them for 15 minutes under the action of an electrostatic field to ensure that the components are evenly distributed, and obtain a mixture.

[0052] S3: Use computer software to perform three-dimensional modeling of the actual internal structure of the target hollow brick to generate a processing program, then perform preset path planning and input into the control system, then place the mixture obtained in step S2 in the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path, lay the mixture on the laser-assisted additive manufacturing table to form the first layer of raw material, use the laser to emit a high-energy laser beam, and scan the raw material layer according to the preset path through the scanning galvanometer. The energy of the laser beam causes the raw material to melt rapidly and combine into a solid; after the first layer is formed, the feeding system lays another layer of mixture, and repeats the above laser scanning process. Stack layer by layer according to the preset structure until the entire brick is formed.

[0053] S4: Place the formed bricks in an infrared drying device, control the drying temperature at 70°C, and dry for 1.5 hours. Monitor the moisture content of the bricks in real time to ensure uniform drying and avoid cracking and deformation.

[0054] S5: The dried bricks are sent to the sintering furnace, and the temperature reaches 110°C in 30 minutes, then 300°C in 3 hours, and then 800°C in the next 6 hours. Then, the temperature reaches 900°C in 2 hours, and the heating is stopped after keeping warm for 30 minutes. The sintering process is monitored by tomography to understand the internal structure of the sintered bricks, and the structural information is fed back to the laser-assisted additive manufacturing station, so as to adjust the forming process of the hollow bricks to achieve the target structure. After the reaction is completed, the specimen is cooled by itself to obtain the sintered hollow bricks.

[0055] Comparative Example 1: No pretreatment, i.e., step S1, was performed on the phosphogypsum and the oil-based ash, and the other steps were the same as those in Example 1.

[0056] Comparative Example 2: No tomography was performed, and other steps were the same as in Example 1.

[0057] Comparative Example 3: No infrared drying treatment was performed, and other steps were the same as in Example 1.

[0058] Comparative Example 4: The mixture includes 60 parts by weight of phosphogypsum and 20 parts of waste concrete, and the other steps are the same as Example 1.

[0059] The compressive strength, 5h boiling water absorption and porosity of the hollow bricks prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested by conventional methods. The results are shown in Table 1.

[0060] Table 1

[0061] performance Compressive strength (MPa) 5h boiling water absorption rate (%) Porosity (%) Example 1 14.6 18 45 Example 2 14.2 18 45 Example 3 14.4 19 44 Example 4 11.6 18 43 Example 5 12.8 18 42 Comparative Example 1 8.9 25 42 Comparative Example 2 9.6 24 35 Comparative Example 3 8.4 22 36 Comparative Example 4 7.3 25 37

[0062] As can be seen from Table 1, compared with the comparative example, the compressive strength of the hollow bricks prepared by the present invention is significantly improved, and the compressive strength can reach 14.6MPa, with high density and low water absorption, which meets the quality standards of hollow bricks. Among them, since the comparative example 2 does not perform tomography, it will not be possible to timely discover and correct the defects inside the material, so stress concentration may occur during the sintering process, thereby affecting the strength and overall quality of the hollow bricks. In addition, the present invention can manufacture hollow bricks with complex structures according to actual needs, so that they have multifunctionality, such as a structure with specific holes and channels inside, to improve the thermal insulation performance of the bricks, and is suitable for the development of complex structures and multifunctional products.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An additive manufacturing method for waste concrete composite oil-based ash-phosphogypsum-based hollow bricks, characterized in that: The following steps are involved: S1: waste concrete recycled powder, phosphogypsum, oil-based ash and functional additives are mixed, and then mixed evenly by electrostatic field to obtain a mixture; the moisture content of the phosphogypsum is reduced to 2-5% after microwave treatment, and the particles of the oil-based ash are less than 0.3 mm; S2: Using computer software to perform three-dimensional modeling on the actual internal structure of the target hollow brick to generate a processing program, and then perform preset path planning and input it into the control system, and then place the mixed material obtained in step S1 into the feeding system, and use laser-assisted additive manufacturing equipment to perform additive manufacturing according to the preset path to obtain a molded brick; S3: The brick blanks formed in step S2 are subjected to infrared drying to make them dry evenly, and then the dried brick blanks are sent to a sintering furnace for sintering. The sintering furnace is also connected to a tomography laser scanning module, which can detect the internal structure of the hollow bricks and feed back the structural information to the control system of the laser-assisted additive equipment, so as to adjust the relevant parameters in the next hollow brick forming process to achieve the target structure. After the sintering reaction is completed, the hollow brick can be obtained after the specimen cools down by itself.

2. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1 is characterized in that: The mixture comprises the following components in parts by weight: 35-50 parts of phosphogypsum, 30-45 parts of waste concrete, 10-20 parts of oil-based ash and 5-10 parts of functional additives.

3. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1 is characterized in that: The functional additives include one or more of silicon dioxide, bauxite or zirconium oxide.

4. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1 is characterized in that: During the microwave treatment, the microwave frequency is 2400-2500 MHz, and the treatment time is 5-10 minutes.

5. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1 is characterized in that: The electrostatic field action time is 10 to 20 minutes.

6. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1 is characterized in that: The infrared drying process has a drying temperature of 60-80° C. and a drying time of 1-2 hours.

7. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1 is characterized in that: The sintering treatment means: firstly, the temperature reaches 100-120°C in 20-30 minutes, then the temperature reaches 300-310°C in 2.5-3 hours, then the temperature reaches 800-900°C in 5-6 hours, and then the temperature reaches 950-1000°C in 1.5-2 hours and keeps warm for 20-30 minutes.

8. The additive manufacturing method of waste concrete composite oil-based ash-phosphogypsum-based hollow bricks according to claim 1, characterized in that: The relevant parameters in step S3 include laser power, scanning speed, powder feeding rate, layer thickness or powder spreading speed.

9. The hollow brick prepared according to the method according to any one of claims 1 to 8.

10. Use of the hollow brick according to claim 9 in the construction of frame structure buildings.

Citation Information

Patent Citations

  • Sintered hollow clay brick for severe cold region and manufacturing method of sintered hollow clay brick

    CN105948698A

  • Solid waste-based baking-free environment-friendly hollow brick and preparation method thereof

    CN111848077A

  • Forming method of cement, cement-based composite material and ceramic refined products

    CN104191495A

  • Method for preparing fired brick prepared by oil-based drill cutting residues

    CN105967649A